UTILIZING NOVEL IN THE READING CLASS TO EXPLORE STUDENTS’ VIEWPOINT OF ITS EFFECTIVENESS - Oktaviari Ayu Sasalia; Fatimah Mulya Sari (fsip.teknokrat.ac.id, 2020)
The use of novel on reading skills was important as an efficient and effective media. The novel helped students evaluate their reading skills. This research aimed to investigate student’s perceptions of the use of novels on reading skills. This research was a descriptive qualitative type. The subject of this research was English education students whose numbers were adjusted to the needs of the research, 22 students. This study was conducted at Universitas Teknokrat Indonesia, Bandar Lampung. The instrument of data collection used a questionnaire and interview. The data analysis method was descriptive qualitative. The results showed participants had a positive perception toward using interactive instruction with authentic literary texts, such as novels, on their reading ability. Hence, it can be concluded that the use of English novels can be an alternative way to improve their reading skills in the English learning process.